HUBUNGAN PENGETAHUAN TENTANG PILAR 1 DAN PILAR 2 DALAM SANITASI TOTAL BERBASIS MASYARAKAT (STBM) DENGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI KELURAHAN KEBON BESAR, KECAMATAN BATUCEPER, KOTA TANGERANG - Aloysius Prihastomo Wibowo; Yusriani Sapta Dewi (JURNAL TECHLINK, 2022)
Healthy is the right of every individual to be able to do all daily life activities. To be able to live a healthy life, wmust have Clean and Healthy Living Behavior (PHBS). Clean and Healthy Living Behavior (PHBS) is a form ofcommunity empowerment that is conscious, willing and able to practice PHBS. The method used in the study icorrelational which aims to know the relationship between knowledge and attitudes with clean and healthy livinbehaviors at Kelurahan Kebon Besar, Kota Tangerang. In addition, this study also aims to find out the physicacondition of basic sanitation facilities in Kelurahan Kebon Besar. The subject in this study is RT 02 and RT 0RW 004 Kelurahan Kebon Besar, Kecamatan Batuceper, Kota Tangerang. The results of the double regeresanalysis showed a significant value of 0.151<0.05, so it can be concluded that there is a relationship of knowledgand attitude with clean and healthy living behaviors of Kebon Besar villagers about basic sanitation with PHBS.The physical condition of basic sanitation of Kebon Besar Subdistrict Batuceper, Tangerang based oobservations such as water, trash cans, toilets and SPAL still does not meet the standards of school sanitatiofacilities according to the Decree of the Minister of Health of the Republic of Indonesia Numbe1429/MENKES/SK/XII/2006 on guidelines for the implementation of school environmental health. Poor sanitatiowill cause various diseases such as diarrhea, toothache, skin pain and worms. Good clean and healthy livingbehavior of students is not followed by standard sanitation facilities in schools so there are still many studentswho are sick